1989
DOI: 10.1073/pnas.86.11.3963
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cytochrome P-450b/e gene expression by a heme- and phenobarbitone-modulated transcription factor.

Abstract: The cloned DNA fragment of the cytochrome P-450b/e gene containing the upstream region from position -179 through part of the first exon is faithfully transcribed in freeze-thawed rat liver nuclei. Phenobarbitone treatment of the animal strikingly increases this transcription, and the increase is blocked by cycloheximide (protein synthesis inhibitor) or CoCl2 (heme biosynthetic inhibitor) treatment of animals. This picture correlates very well with the reported cytochrome P-450b/e mRNA levels in vivo and run-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Yet, even this profound heme depletion had no effect on PB-mediated transcriptional activation of rat CYP2B1 and CYP2B2 genes. Our studies, which used a model of an even more severe hepatic heme pool depletion and highly sensitive quantitative PCR analyses that could distinguish between the highly homologous CYP2B1 and CYP2B2 genes, support previous conclusions that heme is not required for PB-mediated transcriptional activation of either P450 (Srivastava et al, 1989;Sinclair et al, 1990;Jover et al, 2000), as proposed previously (Dwarki et al, 1987;Rangarajan and Padmanaban, 1989).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Yet, even this profound heme depletion had no effect on PB-mediated transcriptional activation of rat CYP2B1 and CYP2B2 genes. Our studies, which used a model of an even more severe hepatic heme pool depletion and highly sensitive quantitative PCR analyses that could distinguish between the highly homologous CYP2B1 and CYP2B2 genes, support previous conclusions that heme is not required for PB-mediated transcriptional activation of either P450 (Srivastava et al, 1989;Sinclair et al, 1990;Jover et al, 2000), as proposed previously (Dwarki et al, 1987;Rangarajan and Padmanaban, 1989).…”
Section: Discussionsupporting
confidence: 75%
“…Just one group to date has advocated a positive role for heme in CYP2B transcriptional activation (Dwarki et al, 1987;Rangarajan and Padmanaban, 1989). Two other research teams having examined this possibility concluded that heme is not involved in CYP2B transcriptional activation (Hamilton et al, 1988;Srivastava et al, 1989;Sinclair et al, 1990).…”
mentioning
confidence: 99%
“…Run-on Transcription-This was carried out by the procedure of Guertin et al (19) and has been described (3,4). Briefly, nuclei were incubated with 200 Ci of [␣-…”
Section: Methodsmentioning
confidence: 99%
“…Studies in this laboratory have led to the identification of a positive cis-acting element (Ϫ69 to Ϫ98 nt) and a negative cis-acting element (Ϫ126 to Ϫ160 nt) in the near 5Ј-upstream region of the CYP2B1/B2 gene (3)(4)(5). The positive element includes the 17-base pair PB-responsive consensus element, referred to as Barbie Box, identified first by Fulco and co-workers (6 -8) in Bacillus megaterium, rat, mice, and other organisms of barbiturate inducible cytochrome P-450 and other proteins.…”
mentioning
confidence: 99%
“…Heme also directly regulates various molecular and cellular processes for systems that use or sense oxygen. For example, heme stimulates the expression of globin chains in erythroid cells and cytochrome P-450 in hepatic cells (6,9,36), activates protein synthesis through the heme-regulated inhibitor kinase (7), and regulates the transport of numerous enzymes and the assembly of hemoglobin and cytochrome complexes (24,31). The roles of heme are largely conserved from yeast to humans, and recent evidence indicates that heme might regulate diverse processes through similar mechanisms (24,48).…”
mentioning
confidence: 99%